ILLICIT TRAFFICKING OF RADIOACTIVE SOURCES: EXPERIENCES WITH FAKE MATERIALS IN TANZANIA - Pantaleo, Peter; Kifanga, Leonard D; Mkilaha, Iddi S. N (Tanzania Journal of Engineering and Technology, 2018)
Radioactive materials although are very useful, they are one of the catastrophic sources of mass destruction if misused. These materials have a number of positive uses which makes them very essential in our modern society. Incidences such as the bombings of the US Embassies in East Africa, the September 11, and many others had formed a basis for international responsive actions to control illicit trafficking of Radioactive and Nuclear Materials. The aim of this work is to track the movements and subsequently uses of these materials. Tanzania is one of the countries where International Nuclear Safeguards protocols are fully operational and observed. In the efforts of control, a number of institutions have been mobilized nationally to the. While these control efforts are enforced, it is observed that several routes and different radioactive purported sources are imported to Tanzania. Although most of the motives of illegal trafficking intercepted have indication of radioactivity through marking and signs, there are cases where the material has been falsified. On the other hand, the motive behind appears to be not only for use but rather illegal dealings such as trading. This paper sites these incidences, their causes and influences on the control and proposes way forward.